Konsiderasi Analgesi Opioid pada Pasien Geriatri - Mahmud; Sudadi; Adityo, Galang Martin (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Based on the changing demographics of geriatrics today, it is expected that there will be an increase in demand for various surgical services, including vascular surgery and general surgery. DI Yogyakarta (14.71 percent) is the city with the largest geriatric population in Indonesia. In the geriatric age group, there are changes related to physiological functions, pharmacokinetics and pharmacodynamics. The use of opioids requires a 25-50% lower initial dose than the adult age group. The administration of opioids in geriatrics needs to consider: the type of opioid group, the level of toxicity, monitoring pharmacological effects and side effects that occur closely after the initial dose, and rotating opioids that allow the use of lower doses.